Cultivatable Bacteriota of Chronic Wound of Patients with Diabetic Foot Syndrome with Critical Limb Ischemia Based on Wound Biopsy in Peri-Revascularization Period - Syedah Sarah Hussaini; Fran Dominic Grubesa; Mateusz Gajda; Martyna Schönborn; Katarzyna Bogucka; Mikołaj Maga; Paweł Maga; Jadwiga Wójkowska-Mach (Microbiology Research)
Diabetic foot syndrome is often associated with inflammation. The aim of this study was to evaluate the impact of improved blood supply on the change in the clinical status and culturable bacteriota of chronic wounds. Patients with diabetic foot and peripheral arterial disease with a Rutherford score of 5 or 6 were included (n = 23). The blood supply to the limb was assessed with laboratory tests and two time-point qualitative cultures using a wound biopsy. The baseline parameters of the blood supply to the limb were Transcutaneous Oxygen Perfusion (TCPO2) of 15.0 mmHg, an Ankle Brachial Index (ABI) of 0.7, and a Toe Brachial Index (TBI) of 0.1, with an average Wound, Infection, Inflammation (WIfI) score of 5.7 (high). The most frequently isolated pathogens were Staphylococcus aureus (26.1%), followed by the Enterobacteriaceae family and Pseudomonas spp. (13.0%, each). Negative cultures were present in 47.8% (n = 11). The control parameters of blood supply improved; TCPO2 was 38.5 mmHg, the ABI was 0.9, and the TBI was 0.3, with a reduction in the average WIfI score to 3.7 (mild), while total colony-forming units (CFUs) increased by 13.5%. No cases of reocclusion or restenosis were observed during the study; however, small amputations were performed in two patients (8.7%). Five (21.7%) ulcers were significantly reduced and two (8.7%) progressed, while a negative culture at follow-up was obtained in five fewer patients than at baseline and nine patients presented growth despite having an initial negative result. Quantitative reduction was obtained in four (17.4%) cases. Pathogen distribution at follow-up resembled baseline findings. Optimizing clinical environments (enhancing blood flow and controlling inflammation) in general over focusing singularly on microbiota composition or revascularization seems to be crucial and arguably outweighed the impact of microbial change alone; in particular, reperfusion may increase the conditions to bacterial growth at the first stage.